2019
DOI: 10.1186/s13287-019-1321-y
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration flufenamic acid enhances osteogenic differentiation of mesenchymal stem cells and suppresses bone loss by inhibition of the NF-κB signaling pathway

Abstract: Background As the representative of fenamic acids, an important group of NSAIDs, flufenamic acid (FFA) has been used for anti-inflammation and analgesia in the clinic. Recently, researches have focused on the role of some members of NSAIDs in promoting osteogenesis. However, little attention has been paid to the subgroup of fenamic acids, and it remains unclear whether FFA and other fenamic acids could regulate mesenchymal stem cells’ (MSCs) lineage commitment and bone regeneration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…However, Oil red O staining showed that 200 μM FFA inhibited adipogenesis better than 100 μM FFA. This may be because 200 μM FFA also inhibited the proliferation of hMSCs, which has been documented in our previous study [25]. Human ASCs and hBMMSCs displayed similar results both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, Oil red O staining showed that 200 μM FFA inhibited adipogenesis better than 100 μM FFA. This may be because 200 μM FFA also inhibited the proliferation of hMSCs, which has been documented in our previous study [25]. Human ASCs and hBMMSCs displayed similar results both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…This might be because they are both populations of postnatal tissue-specific stem cells with similar gene expression profiles and display similar characteristics [28]. We found that low concentrations of FFA promote osteogenesis of hMSCs [25], and adipogenic differentiation is generally inhibited when osteogenic differentiation is promoted. The results of our present study are in agreement with our previous report.…”
Section: Discussionmentioning
confidence: 71%
“…The fibrous glial scar formed by infiltrated inflammatory cells (including microglia, fibroblasts, and reactive astrocytes) limits axon regeneration across the lesion [ 37 , 38 ]. The scar tissue not only exerts a protective effect by limiting the spread of inflammation and secondary damage to adjacent intact tissue but also serves as an inhibitory barrier for axon regeneration [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDA expression was increased and SOD expression was decreased in CLP‐ or LPS‐induced sepsis rats and FFA down‐regulated the MDA expression and up‐regulated the SOD expression in this study. FFA could also improve the osteogenic differentiation and Vibrio cholerae ‐induced diarrhea by inhibiting the NF‐κB signaling pathway (Liu et al, 2019; Pongkorpsakol et al, 2017). We speculate that FFA alleviate the lung injury induced by sepsis through NF‐κB signaling pathway, which might be investigated in the further study.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, FFA played an antidiarrheic role by inhibiting the inflammatory response mediated by NF‐κB (Pongkorpsakol et al, 2017). A study reported that low concentration of FFA promoted osteogenic differentiation of mesenchymal stem cells and inhibited bone loss by inhibiting the NF‐κB signaling pathway (Liu et al, 2019). Through the prediction of STITCH website, the FFA‐related protein, AKR1C3, was found.…”
Section: Introductionmentioning
confidence: 99%